2015
DOI: 10.1111/jcpt.12313
|View full text |Cite
|
Sign up to set email alerts
|

Post-operative infection of endoscopic submucosal dissection of early colorectal neoplasms: a case-controlled study using a Japanese database

Abstract: Summary What is known and objective Endoscopic submucosal dissection of early colorectal neoplasms (ESD‐ECN) is known to be an operation with risk of contamination, possibly requiring pre‐operative antimicrobial prophylaxis for the prevention of post‐operative infection. However, an evaluation of the need for pre‐operative antimicrobial prophylaxis for ESD‐ECN has yet to be reported. The objective of this study was to determine whether pre‐operative antimicrobial prophylaxis is associated with a reduced incide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 8 publications
0
7
0
Order By: Relevance
“…On the other hand, a more recent multicenter RCT including 380 patients showed that perioperative antibiotics did not significantly decrease the incidence of PEECS, at 4.7 % in the antibiotic group versus 7.5 % in the nonantibiotic group ( P = 0.209) 195 . Another large retrospective case–control study from Japan showed that the post-ESD infection rate was low (1.2 %) and that antimicrobial prophylaxis did not prevent postoperative infection (OR 0.73, 95 %CI 0.08–6.61) 196 . In this regard, another study identified cecal location (OR 14.5), presence of submucosal fibrosis (OR 2.8), and female sex (OR 2.6) as independent risk factors for PEECS 197 .…”
Section: Additional Methods To Prevent Adverse Eventsmentioning
confidence: 99%
“…On the other hand, a more recent multicenter RCT including 380 patients showed that perioperative antibiotics did not significantly decrease the incidence of PEECS, at 4.7 % in the antibiotic group versus 7.5 % in the nonantibiotic group ( P = 0.209) 195 . Another large retrospective case–control study from Japan showed that the post-ESD infection rate was low (1.2 %) and that antimicrobial prophylaxis did not prevent postoperative infection (OR 0.73, 95 %CI 0.08–6.61) 196 . In this regard, another study identified cecal location (OR 14.5), presence of submucosal fibrosis (OR 2.8), and female sex (OR 2.6) as independent risk factors for PEECS 197 .…”
Section: Additional Methods To Prevent Adverse Eventsmentioning
confidence: 99%
“…Delayed bleeding was defined as clinical evidence of bleeding that occurred after ER, as evidenced by hematemesis or melena, a decline in hemoglobin levels of more than 2.0 g/dL within 24 hours, or the need for endoscopic therapy ( 22 ). Delayed perforation was verified through X-ray or CT. Postoperative infection was determined by a postoperative body temperature exceeding 37.5°C and/or an increase in inflammatory indicators such as blood routine, CRP, or calcitonin ( 23 ). R0 resection was defined as the surgical removal of a tumor with no residual cancerous tissue detected in the margins of the excised tissue, as confirmed by histological examination of the specimen’s radial and deep margins ( 24 ).…”
Section: Methodsmentioning
confidence: 99%
“…A diagnosis of delayed hemorrhage was confirmed by emergency endoscopy, and a diagnosis of delayed perforation was confirmed by X-ray or CT. Postoperative infection was defined as a postoperative body temperature >37.5°C, accompanied by indicators of inflammation on laboratory testing (routine blood data, high C-reactive protein concentration, or high calcitonin concentration. 14 An R0 resection was defined on the basis of histological examination of the lateral and vertical margins, which showed no residual tumor. 15 …”
Section: Methodsmentioning
confidence: 99%